THE EFFECT OF SHARIA COMPLIANCE ON MEMBER SATISFACTION AT BMT GUMARANG AKBAR SYARIAH MATARAM - Isya Fawatihussuari; Baiq Ari Yusrini; Nurul Susianti (IQTISHADUNA, 2022)
This study aims to determine the effect of sharia compliance on member satisfaction at BMT Gumarang Akbar Syariah Mataram. The research method used in this research is quantitative. The sample used as many as 97 respondents consisting of members in BMT Gumarang Akbar Syariah. Data collection techniques using questionnaires and documentation. The data analysis techniques used are validity test, reliability test, classical assumption test; heteroscedasticity, normality and hypothesis testing with simple linear analysis with the help of SPSS. The results show that sharia compliance has a positive effect on member satisfaction with a coefficient value of 9.061. The results of R Square show a value of 46.4%, meaning that the quality of the two independent variables contributes greatly to this study. From the test results it can be concluded that sharia compliance has a positive and significant effect on member satisfaction.